Combination Treatment with Depressor Anguli Oris Myectomy and Pedicled Buccal Fat Pad Flap for Sequelae of Facial Paralysis: Case Reports - Nakao, Ko; Matoba, Eri; Sakuma, Hisashi (Archives of Plastic Surgery, 2025)
Facial paralysis sequelae result in functional and cosmetic deficits. Myectomy for facial contractures has been reported, and recently, selective myectomy of the smile antagonists (depressor anguli oris [DAO]) for perioral synkinesis has gained attention. Although less invasive, this approach can lead to postoperative depressed deformities of the myectomy site. We report two cases of facial nerve paralysis. In one case, DAO myectomy was performed for synkinesis with the upper lip levator muscles. In the other, the DAO and depressor labii inferioris were myectomized for facial contractures centered on the lower lip. A pedicled buccal fat pad flap was elevated to cover the myectomy defect, preventing postoperative depressed deformity. One year postoperatively, no depressed deformities were observed; lower lip symmetry and oral commissure movement improved, achieving a natural smile. As the procedure involves the transfer of vascularized blood-rich buccal fat, the risk of postoperative induration and contracture is lower than that with fat injections.
Keywords: selective myectomy; depressor anguli oris; depressor labii inferioris; pedicled buccal fat pad flap